Serum-Urine Matched Metabolomics for Predicting Progression of Henoch-Schonlein Purpura Nephritis - Zhang, Qian; Lai, Ling-Yun; Cai, Yuan-Yuan; Wang, Ma-Jie; Ma, Gaoxiang; Qi, Lian-Wen; Xue, Jun; Huang, Feng-Qing (Frontiers in Medicine, 2021)
Henoch-Schonlein purpura nephritis (HSPN) is a common glomerulonephritis secondary to Henoch-Schonlein purpura (HSP) that affects systemic metabolism. Currently, there is a rarity of biomarkers to predict the progression of HSPN. This work sought to screen metabolic markers to predict the progression of HSPN via serum-urine matched metabolomics. A total of 90 HSPN patients were enrolled, including 46 HSPN (+) patients with severe kidney damage (persistent proteinuria >0.3 g/day) and 44 HSPN (-) patients without obvious symptoms (proteinuria <0.3 g/day). Untargeted metabolomics was determined by liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-Q/TOF-MS). A total of 38 and 50 differential metabolites were respectively identified in serum and urine from the comparison between HSPN (+) and HSPN (-) patients. Altered metabolic pathways in HSPN (+) mainly included glycerophospholipid metabolism, pyruvate metabolism, and citrate cycle. A panel of choline and cis-vaccenic acid gave areas under the curve of 92.69% in serum and 72.43% in urine for differential diagnosis between HSPN (+) and HSPN (-). In addition, the two metabolites showed a significant association with clinical indices of HSPN. These results suggest that serum-urine matched metabolomics comprehensively characterized the metabolic differences between HSPN (+) and HSPN (-), and choline and cis-vaccenic acid could serve as biomarkers to predict HSPN progression.